Strengthening Anti-SLAPP Procedural Provisions in Indonesia: A Normative-Comparative Study and Its Implementation in the Decision of PT Bangka Belitung No. 21/Pid/2021/PT BBL - Muhammad Kurnia; Rendy Rendy; Arief Hidayat (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Public participation is a foundational pillar of democratic governance, particularly in protecting and sustainably managing the environment. Within this framework, every citizen has the right to engage in environmental advocacy without fear of criminal prosecution or civil lawsuits. This legal protection, as stipulated in Article 66 of Law No. 32 of 2009 on Environmental Protection and Management (UU PPLH), embodies the concept of Anti-Strategic Litigation Against Public Participation (Anti-SLAPP). However, the Indonesian Anti-SLAPP provision continues to face substantial procedural and substantive weaknesses, resulting in persistent criminalization and judicial harassment against environmental human rights defenders. This study aims to critically analyze procedural deficiencies in the Anti-SLAPP mechanism in Indonesia by comparing it with California (United States) and the Philippines, two jurisdictions that have developed advanced procedural safeguards to ensure public participation. Employing a normative juridical method and comparative legal analysis, this paper explores both international and domestic frameworks governing Anti-SLAPP principles. In addition, this article contextualizes the landmark Decision of the Bangka Belitung High Court No. 21/Pid/2021/PT BBL, delivered on May 10, 2021, which, for the first time, recognized Anti-SLAPP reasoning in a criminal case and acquitted the defendants, Robandi, Muhammad Yusuf, Syamsul Effendi, Heti Rukmana, and Aditama, who had been criminalized for their environmental advocacy. This judicial precedent demonstrates the transformative potential of Article 66 UU PPLH as a progressive legal safeguard. It underscores the urgent need for a coherent procedural framework to operationalize Anti-SLAPP protections in Indonesia